Effect of integrating chickpea varieties with insecticides for the management of pod borer (Helicoverpa armigera Hubner) (Lepidoptera: Noctudae) - Dagne Kora; Ermias Teshome (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Chickpea (Cicer arietinum L.) is the world's second most important grain legume after common bean (Phaseolus vulgaris L.). Ethiopia is considered as a secondary center of genetic diversity for chickpea. The field experiment was conducted at Ginir district with the objectives to evaluate the effective management option against chickpea pod borer and to determine the optimum frequencies of the insecticide for the management of chickpea pod borer. The experiment was conducted using two chick pea varieties; Habru (more preferred) and Arerit (less preferred) and two insecticide Highway 50% EC (400ml/ha) and Nimbicidine (3lt/ha). The result revealed that both insecticides are effective against pod borer even if they have slight percent larval reductions. The pod borer damage reduction ranged from 56.83% to 69.94% and on Highway 50% EC treated plots as compared to the control on Habru variety. On the variety Arerit up to 76.30% larval reduction on the Highway 50% EC treated plot was occurred as compared to control. The minimum 36.17% larval reduction was occurred on the plot treated with Nimbicidine on the variety Habru. The Maximum percent of seed yield (57.95% and 57.95%) increased over check was occurred by Highway 50% EC one and two times treaded plots on the variety Arerit, respectively. The plot sprayed one and two times with Highway 50%EC gave the maximum net return ETB 178,959.8ha-1and ETB 178,402ha-1 on the variety Arerti and the unsprayed plot of the variety Arerti gave the minimum net returns ETB 15,054ha-1. It is recommended that these insecticides with specially Arerit variety are suggested to the growers for management of the pod borer population below economic threshold level under field conditions.